Drift of the sensitive direction of Hall-effect devices in (1 0 0)-silicon caused by mechanical shear stress. (December 2020) - Ausserlechner, Udo; Holliber, Michael; Kollmitzer, Benjamin; Heinz, Richard
Highlights: Shear stress in crystals tilts the direction of maximum magnetic field response. This gives crosstalk of orthogonal magnetic field components in the Hall output. This effect is notable for Vertical Hall devices in plastic encapsulated packages. It may lead to an orthogonality error in Hall based magnetic angle sensors. The idea of a compensation circuitry with a shear stress sensor is introduced. Abstract: Conventional Hall effect devices are designed to respond to a single magnetic field component in 3D space. However, if plastic encapsulated Hall effect devices in cubic crystals are exposed to poorly defined and unstable mechanical shear stress, small portions of unwanted, perpendicular magnetic field components will show up in the Hall output signals. Mathematically, any such crosstalk – may it originate from mechanical stress or not – can be expressed as a Taylor series in powers of the magnetic field. The even powers are the well known planar Hall effect at zero mechanical stress. In practice powers of even order are irrelevant, because they are eliminated by the widely used spinning current schemes. In this paper we address the odd powers of the magnetic crosstalk and their drift versus mechanical stress. The effect is small for Hall plates but large for Vertical Hall devices in (1 0 0)-silicon. It is fully described by piezo-resistance and piezo-Hall tensors. We present results of numerical simulations and measurements. Thin devices are less affected than thick devices. If magnetic angle sensors are made of Vertical Hall devices, in-plane shear stress leads to small orthogonality errors. This article lays the foundations for compensation circuits to eliminate such shear-stress induced orthogonality errors.